An approach to age and growth of south Atlantic swordfish (Xiphias gladius) stock - Quelle, Pablo; González-Blázquez, Florencio; Ruiz, Marta; Valeiras, Julio; Gutiérrez-Martín, Luis Óscar; Rodriguez-Marin, Enrique; Mejuto-García, Jaime (2014)
A first growth function was estimated for the South Atlantic swordfish stock. A total of 406 anal fins were collected from 2006 to 2013. Fins were classified into three types and the most common, type A, was selected. Biometric relationships among several ray section measurements and lower jaw fork length were analysed. A detailed methodological description for swordfish age interpretation has been developed. Inconclusive results have been obtained when indirect validation test, as edge type and marginal increment ratio analysis, were applied. Mean size at age and growth parameters were estimated using the Standard Von Bertalanffy growth model (VBGM) (L∞= 358.7, k= 0.092, t0= -1.929), which showed the best fit in comparison with other VBGMs.